Dissociation between the pharmacokinetics and pharmacodynamics of once‐daily rivaroxaban and twice‐daily apixaban: a randomized crossover study. (14th September 2017) - Kreutz, R.; Persson, P. B.; Kubitza, D.; Thelen, K.; Heitmeier, S.; Schwers, S.; Becka, M.; Hemmrich, M.
Abstract : Essentials In this crossover study the anticoagulant effects of rivaroxaban and apixaban were compared. Healthy volunteers received rivaroxaban 20 mg once daily or apixaban 5 mg twice daily. Rivaroxaban was associated with more prolonged inhibition of thrombin generation than apixaban. Rivaroxaban induced a clear prolongation of prothrombin time and activated partial thromboplastin time. Summary: Background: The anticoagulant actions of the oral direct activated factor Xa inhibitors, rivaroxaban and apixaban, have not previously been directly compared. Objectives: To compare directly the steady‐state pharmacokinetics and anticoagulant effects of rivaroxaban and apixaban at doses approved for stroke prevention in patients with non‐valvular atrial fibrillation. Methods: Twenty‐four healthy Caucasian male volunteers were included in this open‐label, two‐period crossover, phase 1 study (EudraCT number: 2015‐002612‐32). Volunteers were randomized to receive rivaroxaban 20 mg once daily or apixaban 5 mg twice daily for 7 days, followed by a washout period of at least 7 days before they received the other treatment. Plasma concentrations and anticoagulant effects were measured at steady state and after drug discontinuation. Results: Overall exposure was similar for both drugs: the geometric mean area under the plasma concentration–time curve for the 0–24‐h interval was 1830 μg h L −1 for rivaroxaban and 1860 μg h L −1 for apixaban. Rivaroxaban was associated with greater inhibition of endogenous thrombin potential (geometric mean area under the curve relative to baseline during the 0–24‐h interval: 15.5 h versus 17.5 h) and a more pronounced maximal prolongation relative to baseline of prothrombin time (PT) (1.66‐fold versus 1.14‐fold) and activated partial thromboplastin time (APTT) (1.43‐fold versus 1.16‐fold) at steady state than apixaban. Conclusions: Despite similar exposure to both drugs, rivaroxaban 20 mg once daily was associated with greater and more sustained inhibition of thrombin generation than apixaban 5 mg twice daily. Sensitive PT and APTT assays can be used to estimate the anticoagulant effects of rivaroxaban.